EFEKTIVITAS PENYALURAN KREDIT USAHA RAKYAT PT. BRI (PERSERO) UNIT BLAHKIUH TERHADAP PRODUKTIVITAS UKM DAN PENDAPATAN UKM PENERIMA KUR DI KECAMATAN ABIANSEMAL - lastina, ni luh made ayu danni; Budhi, Made Kembar Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018DO - 10.24843/EEB.2018.v07.i04.p02, 2018)
This study aims to determine the effectiveness of business credit distribution of Bank BRI (Persero) Unit Blahkiuh to SME productivity and SME revenue recipient KUR in District Abiansemal. Analyzer used is SEM analysis of Partial Least Square (PLS). This study uses primary data types and data collection is done through the distribution of questionnaires to SMEs who take KUR at Bank BRI Unit Blahkiuh as much as 100 respondents.The analysis results show (i) The effectiveness of KUR distribution of Bank BRI Unit Blahkiuh has a positive and significant effect on SME productivity in Abiansemal Sub-district. (ii) SME productivity has a positive and significant impact on SME revenue in Abiansemal Sub-district. (iii) The effectiveness of KUR distribution of Bank BRI Unit Blahkiuh has a positive and significant effect on SME revenue through SME productivity in Kecamatan Abiansemal.